2020
DOI: 10.21037/cdt-20-197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes between robotic and thoracoscopic mitral valve repair

Abstract: Background: To compare the clinical outcomes and hospital cost of robotic versus thoracoscopic approaches to mitral valve plasty (MVP). Methods:We retrospectively analyzed patients who received minimal invasive MVP between 2007 January and 2020 January at our department. The basic characteristics, echocardiography, surgical data, postoperative adverse events and hospital cost of the patients were collected. The primary outcomes of this study were direct hospital cost and 30-day outcomes, including the operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 11 publications
0
32
3
Order By: Relevance
“…We compared the short-term and midterm benefits of total robotic MVP and total thoracoscopic MVP with a retrospective study and concluded that both robotic and thoracoscopic MVP is safe and reliable. 3 In contrast to the findings of the study by Barac et al, the robotic technique had a shorter operative time in our study, while the thoracoscopic procedure was more advantageous in terms of ICU time, transfusion rates, hospital costs, and satisfactory clinical benefits were achieved in both groups at subsequent follow-up.…”
contrasting
confidence: 99%
“…We compared the short-term and midterm benefits of total robotic MVP and total thoracoscopic MVP with a retrospective study and concluded that both robotic and thoracoscopic MVP is safe and reliable. 3 In contrast to the findings of the study by Barac et al, the robotic technique had a shorter operative time in our study, while the thoracoscopic procedure was more advantageous in terms of ICU time, transfusion rates, hospital costs, and satisfactory clinical benefits were achieved in both groups at subsequent follow-up.…”
contrasting
confidence: 99%
“…Despite the thorough comparisons between MVr via minimally invasive techniques and via sternotomy, data on direct comparison of perioperative complications between robotic MVr and nonrobotic MVr are sparse. To date, only two studies directly compared robotic MVr to nonrobotic MVr 13,14 . Wei et al reported that robotic MVr had a shorter CPB time and aorta clamping time, but had more blood transfusions (63% vs. 52%), longer postoperative ventilation time (15 vs. 11 h) and longer ICU stay, while Barac et al reported a longer CPB time and aorta clamping time associated with robotic MVr.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only two retrospective studies compared the operative outcomes of the two techniques. 13,14 We hypothesized that the freedom from reoperation and from recurrent MR is similar after robotic and nonrobotic MVr, as is the long-term survival. In this retrospective cohort study, we sought to analyze the durability of mitral valve repair as evaluated by freedom form reoperations and from MR recurrence of both minimally invasive techniques in patients undergoing mitral valve repair surgery at Mayo Clinic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations